Religion, Suanggi, and Suicide: A Case Study in the City of Ambon from the Perspective of Religious Studies - Gaspersz, Steve G.C.; Souisa, Nancy N.; Latuheru, Rido D. (Balai Penelitian dan Pengembangan Agama Semarang, 2020)
During 2017-2019 a few cases of suicide amongst Christian teenagers in the city of Ambon have been linked to the inﬂ uence of “suanggi” that has connotations of being the representation of an evil supernatural power. By using the qualitative research method with a case study approach, the article is focused on the religious reactions of the Christian community in their understanding and rationalization of these two phenomena. Data is collected through Focus Group Discussion (FGD) and personal interviews. All collected qualitative data are analyzed by social hermeneutical analysis. The results of the study have shown that: (1) Social change that occurred amongst the people of Ambon has implications in the shift of traditional order of living values, at the same time clashes between the custodians of cultural traditions and morality (church) have occurred. (2) Within the Ambonese community, religion does not only symbolize certain systems of belief, but also becomes the institution that provides a place for the communal spirit and protects the shared morality through its teachings and the practice of its rituals. (3) The phenomena of suicide amongst teenagers in Ambon, the circulation of information concerning the inﬂuence of “suanggi”, and the reactive response of the Christian community reﬂects the clash between the insistence for social change amongst the urban communities.